1985
DOI: 10.1021/bi00339a012
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and biochemical investigation of the lead(II)-catalyzed hydrolysis of yeast phenylalanine tRNA

Abstract: X-ray diffraction data from monoclinic crystals of yeast tRNAPhe soaked in dilute lead(II) acetate solutions at pH 5.0 and at pH 7.4 have been collected to a resolution of 3 A, and the Pb(II) binding sites have been obtained by difference Fourier analyses. The same three Pb(II) binding sites are observed at both of these pH values. At pH 7.4 an extra peak of negative electron density appears on the difference map close to one of the Pb(II) binding sites and at the position of phosphate-18, indicating cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
210
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(222 citation statements)
references
References 88 publications
11
210
1
Order By: Relevance
“…The lupine tRNA vh" having the same nucleotide sequence as yeast tRNA eh" in both the T-loop and Dloop, i.e. at the Pb-ion-binding site and at the cleavage site [8][9][10][11], is cleaved with the same strength and specificity. On the other hand, E. coil tRNA Ph~ is significantly more resistant to the reaction with Pb.…”
Section: Lead(ii)-induced Hydrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…The lupine tRNA vh" having the same nucleotide sequence as yeast tRNA eh" in both the T-loop and Dloop, i.e. at the Pb-ion-binding site and at the cleavage site [8][9][10][11], is cleaved with the same strength and specificity. On the other hand, E. coil tRNA Ph~ is significantly more resistant to the reaction with Pb.…”
Section: Lead(ii)-induced Hydrolysismentioning
confidence: 99%
“…On the other hand, in E. coli tRNA Phe where G45 is replaced by uridine and A44 by guanosine, a series of weak Pb, Eu and Mg-induced cleavages occur in that region. It is, therefore, tempting to assume that due to the above base substitutions a metal-ion-binding site is created in E. coli tRNA Phe that is highly similar for Pb, Eu and Mg ions but different from the Pb2-(Sm4)-binding site in yeast tRNA Phe [8][9][10]18,19].…”
Section: Variable-loop Cleavagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary structure of tRNA anticodon hairpins for which coordinates are deposited in the Nucleic Acid Database (NDB) (Berman et al+, 1992) Brown et al+, 1985;trna04: Sussman et al+, 1978;trna05: Comarmond et al+, 1986;trna06: Westhof & Sundaralingam, 1986;trna07, trna08, trna09: Westhof et al+, 1988;trna10: Hingerty et al+, 1978;pr0004: Nissen et al+, 1999;pr0024: Goldgur et al+, 1997;ptr012: Nissen et al+, 1995+ b In tRNAs, purines represent roughly a little more than 50% of the nucleotides present at position 35 (Auffinger & Westhof, 1998b) as expected from the genetic code and deduced from the 550 tRNAs and 3,704 tDNA gene sequences itemized in the tRNA database (Sprinzl et al+, 1998)+ From the nine available crystallographic structures of yeast tRNA Phe (including the structures extracted from the yeast tRNA Phe /EF-TU and the Thermus thermophilus tRNA Phe /RS complexes where the anticodon loop structure is not altered, ptr012 and pr0024, respectively, see Table 1), it has been inferred that the 29-hydroxyl group of U33 forms a hydrogen bond with the N7 atom of A35 (Fig+ 2)+ This assumes that the hydroxyl (U33)O29-H group points toward the (A35)N7…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the binding of metal ions to RNA was ~ 30. studied for tRNA and it was reported that tRNA had many ~ 20. different binding sites for metal ions [17]. For example, in the ~o-presence of both Pb 2+ and Mg 2+, Pb 2+ coordinated directly to 0 4 of U and N 3 of C in the T loop at the corner of the L-0-structure of tRNA, while Mg 2+ located near the site of Pb 2+ [18]. The two classes of metal ion binding sites were also observed in Tetrahymena self-splicing intron [6,7,19].…”
Section: Discussionmentioning
confidence: 98%